SPECIES COMPOSITION AND TAXONOMIC ANALYSIS OF LEPIDOPTERANS (INSECTA, LEPIDOPTERA) OF AGROECOSYSTEMS OF THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2025)
This article highlights the species composition and taxonomic analysis of the fauna of Lepidoptera insects. The research was carried out from 2012 to 2023 in the agroecosystems of the Fergana Valley. Samples of Lepidoptera insects were collected in farm and household plots in the Fergana, Andijan and Namangan regions. 158 species belonging to 116 genera, 25 families and 15 superfamilies of Lepidoptera insects were identified, which are in a trophic relationship with agricultural plants from the agroecosystems of the Fergana Valley. According to the comparative analysis of taxonomic units, the leading place in agroecosystems belongs to representatives of the Noctuidae family of the Lepidoptera order. In particular, 58 species belonging to families make up 36.7% of the total lepidopteran fauna. According to the species diversity, the number of genera is also numerous (36), and their share in the fauna is 31%. As a result of faunistic studies in the agroecosystems of the Fergana Valley, 55 species belonging to 46 genera of 12 families of the order of Lepidoptera insects were identified for the first time. Among them, 19 species belonging to 18 genera of 6 families, previously not found in the territory of Uzbekistan, are included in the list of those registered for the first time in the entomofauna of our republic. At the same time, 2 species from the Crambidae family in the entomofauna of Central Asia were not previously noted.